Efektivitas Penerapan Check and Balances: Perbandingan Presidensial Indonesia, Filipina, dan Korea Selatan - Mirza Nasution; Geofani Milthree Saragih (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study stems from the urgency of maintaining the stability of the presidential system through the effective implementation of the principle of checks and balances. The research focuses on a comparison of the implementation of this principle in three countries with presidential systems, namely Indonesia, the Philippines and South Korea. The main problem is how the checks and balances mechanism is designed and implemented in the constitutional structure of each country, and how effective the mechanism is in preventing the domination of power by one state institution. The method used is normative juridical research with a comparative legal approach, through analysis of legislation, judicial decisions, and relevant academic documents. The results show that the effectiveness of checks and balances is highly dependent on constitutional design, political culture, and the strength of countervailing institutions. The Philippines demonstrates an active oversight system, mainly by the legislature and the Supreme Court. South Korea has effective oversight through audit institutions and impeachment procedures. Indonesia still faces challenges in strengthening oversight due to overly harmonious executive-legislative political relations. This research suggests the importance of strengthening the state's institutional structure and acculturating the principle of mutual supervision between branches of power as the main prerequisites for the creation of a healthy, balanced presidential system, and able to prevent the domination of power by one state institution.